2008
DOI: 10.1016/j.jfoodeng.2008.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics and product quality of dried Chempedak

Abstract: a b s t r a c tThe objective of this study was to investigate the drying kinetics of chempedak (Artocarpus integer) at different drying temperatures (50°C, 60°C, 70°C) and slab dimensions. The drying data were fitted to the different semi-theoretical models based on moisture ratio (MR) to predict the drying kinetics. A logarithmic model was found to be the best fit in this study for all the drying temperatures tested. Effective diffusivities were estimated from Fick's 2nd law and the Arrhenius equation was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 30 publications
7
33
0
Order By: Relevance
“…Similar behaviour of D eff has been reported for okra (Doymaz, 2005), aloe vera (Vega et al, 2007) and onions (Mota, Luciano, Dias, Barroca, & Guiné, 2010). However, the diffusivity values obtained in the present study are higher than those reported in literature for other vegetables (Chong et al, 2008;Vega et al, 2007). The reason for this could be the higher initial water content of H. elongata allowing greater diffusion coefficients, since the process of diffusion is favored in products with higher proportions of water and lower proportions of solids (Guiné & Fernandes, 2006).…”
Section: S Gupta Et Al / Lwt -Food Science and Technology XXX (2011supporting
confidence: 83%
“…Similar behaviour of D eff has been reported for okra (Doymaz, 2005), aloe vera (Vega et al, 2007) and onions (Mota, Luciano, Dias, Barroca, & Guiné, 2010). However, the diffusivity values obtained in the present study are higher than those reported in literature for other vegetables (Chong et al, 2008;Vega et al, 2007). The reason for this could be the higher initial water content of H. elongata allowing greater diffusion coefficients, since the process of diffusion is favored in products with higher proportions of water and lower proportions of solids (Guiné & Fernandes, 2006).…”
Section: S Gupta Et Al / Lwt -Food Science and Technology XXX (2011supporting
confidence: 83%
“…(58,61) In Southern Africa, monkey orange fruits are commonly dried by fire and direct sun to fruit rolls, leathers, pound into flour (S. cocculoides) used to cook porridge, referred to locally as "bozo" in Mozambique (30) or re-cooked as a sauce. (62) Sun dried monkey orange pulp can be stored from two months to five years, (63) which makes thermal drying an ideal preservation method due to its affordability for rural communities and as a means to secure continuous fruit availability into the next season.…”
Section: Dryingmentioning
confidence: 99%
“…These characteristics may indicate that dried blueberries reached a rubbery state [34]. It is believed that if the texture of the dried blueberries is softer, the quality is better [36].…”
Section: Mechanical Propertiesmentioning
confidence: 99%